A kind of iron-rich high temperature resistant heat insulation composite material and preparation method thereof

By using a specific proportion of hematite powder and mica powder in the thermally insulating composite material and adding diphenyl silicone glycol to the binder, the poor refractory and mechanical properties of the thermally insulating composite material at high temperatures in the prior art are solved. The poor problem has achieved the improvement of the high temperature and mechanical properties of the material.

CN118955012BActive Publication Date: 2024-12-24HUANENGZHONGTIAN ENERGY EFFLCIENCY TECH GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411447940.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-24
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing iron-rich insulating composite materials have limited fire resistance at high temperatures, and the material structure is prone to deformity, which affects its mechanical properties and limits its application range.

Method used

Use fiber raw materials including basalt, hematite powder, coke, vanadium iron slag and mica powder, as well as binders with silicone modified epoxy resin, silicone copolymer, silica and curing agents, and through reasonable regulation The ratio of hematite powder to mica powder and binder components, especially diphenyl silicone glycol, are added to improve the high temperature and mechanical properties of the insulating composite materials.

Benefits of technology

It significantly improves the high temperature resistance and mechanical properties of thermally insulating composite materials, so that they maintain structural stability and tensile strength in high temperature environments, and is suitable for applications that require high temperature and high mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of thermal insulation materials, and proposes an iron-rich high-temperature resistant thermal insulation composite material and a preparation method thereof. The iron-rich high-temperature resistant thermal insulation composite material comprises fibers and a binder. The raw materials of the fibers comprise the following components in parts by weight: 35-45 parts of basalt, 20-32 parts of hematite powder, 10-16 parts of coke, 4-8 parts of ferrovanadium slag, and 3-18 parts of mica powder; the raw materials of the binder comprise the following components in parts by weight: 8-17 parts of organosilicon-modified epoxy resin, 2-5 parts of siloxane copolymer, 3-6 parts of silicon dioxide, 1-3 parts of curing agent, and 30 parts of solvent. Through the above technical scheme, the problems of poor high-temperature resistance and poor mechanical properties of thermal insulation composite materials in related technologies are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal insulation composite materials, and in particular to an iron-rich high-temperature resistant thermal insulation composite material and a preparation method thereof. Background Art

[0002] Thermal insulation composite materials are materials that can block heat flow transfer. Such materials are widely used in building enclosures, thermal equipment and other fields to resist heat flow transfer, meet specific thermal environment requirements, and effectively save energy. With the continuous development of my country's economy and the continuous improvement of people's requirements for living comfort, thermal insulation composite materials have developed rapidly. At the same time, people have higher and higher requirements for the performance of thermal insulation composite materials, especially fire-resistant thermal insulation performance. Thermal insulation composite materials rich in iron elements are a special thermal insulation composite material that can improve the fire-resistant thermal insulation performance of thermal insulation composite materials to a certain extent. However, at this stage, although thermal insulation composite materials rich in iron elements have certain thermal insulation performance, their high temperature resistance is limited. The material structure is easy to deform at high temperature, which also affects its mechanical properties. It is not suitable for use in an environment where high temperature resistance and high mechanical strength are required at the same time, thereby limiting its application. Therefore, it is of great significance to develop a thermal insulation composite material that is resistant to high temperatures and has good mechanical properties. Summary of the invention

[0003] The present invention provides an iron-rich high-temperature resistant heat-insulating composite material and a preparation method thereof, which solves the problems of poor high-temperature resistance and poor mechanical properties of the heat-insulating composite material in the related art.

[0004] The technical solution of the present invention is as follows:

[0005] The present invention provides an iron-rich high temperature resistant heat insulating composite material, comprising fibers and a binder, wherein the raw materials of the fibers include the following components in parts by weight:

[0006] 35-45 parts of basalt, 20-32 parts of hematite powder, 10-16 parts of coke, 4-8 parts of ferrovanadium slag, 3-18 parts of mica powder;

[0007] The raw materials of the binder include the following components in parts by weight:

[0008] 8-17 parts of organosilicon-modified epoxy resin, 2-5 parts of siloxane copolymer, 3-6 parts of silicon dioxide, 1-3 parts of curing agent, 30 parts of solvent;

[0009] The weight ratio of the fiber to the binder is 100:3-7.

[0010] As a further technical solution, the weight ratio of the hematite powder to the mica powder is 2~5:1.

[0011] When the weight ratio of hematite powder to mica powder is 2-5:1, the high temperature resistance and mechanical properties of the thermal insulation composite material can be further improved by reasonably adjusting the addition amount of hematite powder and mica powder.

[0012] As a further technical solution, the raw materials of the binder also include 1 to 6 parts of diphenylsilanediol.

[0013] Adding diphenylsilanediol to the binder can further improve the mechanical properties of the thermal insulation composite material through the effective combination of diphenylsilanediol and silicone-modified epoxy resin. It is speculated that the reason may be that the connection between the molecular chains of diphenylsilanediol and silicone-modified epoxy resin is tighter, thereby better resisting external forces, thereby further improving the mechanical properties of the thermal insulation composite material.

[0014] As a further technical solution, the weight ratio of the organosilicon-modified epoxy resin to the diphenylsilanediol is 5:1-2.

[0015] When the weight ratio of organosilicon-modified epoxy resin to diphenylsilanediol is 5:1-2, the mechanical properties of the thermal insulation composite material can be further improved.

[0016] As a further technical solution, the content of silicon dioxide in the basalt is 48wt%~52wt%, the content of aluminum oxide is 10wt%~15wt%, and the particle size is 300~360 meshes.

[0017] As a further technical solution, the content of iron oxide in the hematite powder is 65wt%~70wt%, and the particle size of the hematite powder is 200~325 mesh.

[0018] As a further technical solution, the content of vanadium pentoxide in the ferrovanadium slag is 12wt%~14wt%, and the particle size is 200~325 mesh.

[0019] As a further technical solution, the content of silicon dioxide in the mica powder is 55wt%~65wt%, the content of aluminum oxide is 15wt%~20wt%, and the particle size is 400~600 mesh.

[0020] As a further technical solution, the preparation method of the adhesive comprises the following steps: adding the organosilicon-modified epoxy resin, siloxane copolymer, silicon dioxide and curing agent into a solvent, dispersing them evenly, and obtaining the adhesive.

[0021] As a further technical solution, the curing agent is one or both of diaminodiphenylmethane and pyromellitic dianhydride; and the solvent is one or both of toluene and xylene.

[0022] The present invention also provides a method for preparing an iron-rich high temperature resistant heat insulating composite material, comprising the following steps:

[0023] S1, mixing, crushing and melting the raw materials of the fiber to obtain a molten liquid;

[0024] S2, centrifuging and drawing the molten liquid to obtain the fiber;

[0025] S3, spraying the binder on the surface of the fiber, and curing and shaping the fiber to obtain the thermal insulation composite material.

[0026] As a further technical solution, in step S1, the temperature during melting is 1320-1350°C.

[0027] As a further technical solution, in step S3, during the curing molding, the curing temperature is 180-200°C.

[0028] The working principle and beneficial effects of the present invention are:

[0029] In the present invention, the thermal insulation composite material is an iron-rich high-temperature resistant thermal insulation composite material, which has excellent high-temperature resistance and mechanical properties. Hematite powder and mica powder are introduced into the fiber raw material. The synergistic use of hematite powder and mica powder can enhance the stability of the fiber structure, thereby improving its high-temperature resistance and mechanical properties. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the following embodiments and comparative examples, the content of silicon dioxide in the basalt is 50wt%, the content of aluminum oxide is 10wt%, and the particle size is 325 mesh; the content of iron oxide in the hematite powder is 66wt%, and the particle size of the hematite powder is 200 mesh; the content of vanadium pentoxide in the ferrovanadium slag is 13wt%, and the particle size is 325 mesh; the content of silicon dioxide in the mica powder is 56wt%, the content of aluminum oxide is 18wt%, and the particle size is 600 mesh; the model of the silicone-modified epoxy resin is TY-H26; the model of the siloxane copolymer is PCFXM1414T.

[0032] Example 1

[0033] An iron-rich high-temperature resistant heat-insulating composite material comprises fibers and a binder, wherein the raw materials of the fibers comprise the following components in parts by weight:

[0034] 35 parts basalt, 20 parts hematite powder, 10 parts coke, 4 parts ferrovanadium slag, 3 parts mica powder;

[0035] The raw materials of the binder include the following components in parts by weight:

[0036] 8 parts of organosilicon-modified epoxy resin, 2 parts of siloxane copolymer, 3 parts of silicon dioxide, 1 part of pyromellitic anhydride, 30 parts of toluene;

[0037] The preparation method of the adhesive comprises the following steps: adding organic silicon modified epoxy resin, siloxane copolymer, silicon dioxide and pyromellitic anhydride into toluene according to weight parts, dispersing them evenly, and obtaining the adhesive;

[0038] The preparation method of the iron-rich high temperature resistant heat insulating composite material comprises the following steps:

[0039] S1, mixing and crushing the raw materials of the above fibers, and melting them at 1320° C. to obtain a molten liquid;

[0040] S2, centrifuging and drawing the melt to obtain fibers;

[0041] S3. Spray the binder on the fiber surface (the amount of the binder is 3% of the fiber weight), and cure at 180° C. to obtain a thermal insulation composite material.

[0042] Example 2

[0043] An iron-rich high-temperature resistant heat-insulating composite material comprises fibers and a binder, wherein the raw materials of the fibers comprise the following components in parts by weight:

[0044] 40 parts basalt, 22 parts hematite powder, 13 parts coke, 6 parts ferrovanadium slag, 14 parts mica powder;

[0045] The raw materials of the binder include the following components in parts by weight:

[0046] 10 parts of organosilicon-modified epoxy resin, 4 parts of siloxane copolymer, 4 parts of silicon dioxide, 2 parts of pyromellitic anhydride, and 30 parts of toluene;

[0047] The preparation method of the adhesive comprises the following steps: adding organic silicon modified epoxy resin, siloxane copolymer, silicon dioxide and pyromellitic anhydride into toluene according to weight parts, dispersing them evenly, and obtaining the adhesive;

[0048] The preparation method of the iron-rich high temperature resistant heat insulating composite material comprises the following steps:

[0049] S1, mixing the raw materials of the above fibers, crushing them, and melting them at 1335° C. to obtain a molten liquid;

[0050] S2, centrifuging and drawing the melt to obtain fibers;

[0051] S3. Spray the binder on the fiber surface (the amount of the binder is 5% of the fiber weight), and cure at 190° C. to obtain a thermal insulation composite material.

[0052] Example 3

[0053] An iron-rich high-temperature resistant heat-insulating composite material comprises fibers and a binder, wherein the raw materials of the fibers comprise the following components in parts by weight:

[0054] 45 parts of basalt, 32 parts of hematite powder, 16 parts of coke, 8 parts of ferrovanadium slag, 18 parts of mica powder;

[0055] The raw materials of the binder include the following components in parts by weight:

[0056] 17 parts of organosilicon-modified epoxy resin, 5 parts of siloxane copolymer, 6 parts of silicon dioxide, 3 parts of pyromellitic anhydride, and 30 parts of toluene;

[0057] The preparation method of the adhesive comprises the following steps: adding organic silicon modified epoxy resin, siloxane copolymer, silicon dioxide and pyromellitic anhydride into toluene according to weight parts, dispersing them evenly, and obtaining the adhesive;

[0058] The preparation method of the iron-rich high temperature resistant heat insulating composite material comprises the following steps:

[0059] S1, mixing and crushing the raw materials of the above fibers, and melting them at 1350° C. to obtain a molten liquid;

[0060] S2, centrifuging and drawing the melt to obtain fibers;

[0061] S3. Spray the binder on the fiber surface (the amount of the binder is 7% of the fiber weight), and solidify at 200° C. to obtain a thermal insulation composite material.

[0062] Example 4

[0063] The only difference between this embodiment and embodiment 2 is that, in this embodiment, 31 parts of hematite powder and 5 parts of mica powder are added.

[0064] Example 5

[0065] The only difference between this embodiment and embodiment 2 is that, in this embodiment, 24 parts of hematite powder and 12 parts of mica powder are added.

[0066] Example 6

[0067] The only difference between this embodiment and embodiment 2 is that, in this embodiment, 30 parts of hematite powder and 6 parts of mica powder are added.

[0068] Example 7

[0069] The only difference between this embodiment and embodiment 6 is that in this embodiment, the binder further includes diphenylsilanediol, and the amount of diphenylsilanediol added is 1 part.

[0070] Example 8

[0071] The only difference between this embodiment and embodiment 7 is that in this embodiment, 6 parts of diphenylsilanediol are added to the binder.

[0072] Example 9

[0073] The only difference between this embodiment and embodiment 7 is that in this embodiment, 2 parts of diphenylsilanediol are added to the binder.

[0074] Example 10

[0075] The only difference between this embodiment and embodiment 7 is that in this embodiment, 4 parts of diphenylsilanediol are added to the binder.

[0076] Comparative Example 1

[0077] The difference between this comparative example and Example 1 is that in this comparative example, no hematite powder is added, and 23 parts of mica powder are added.

[0078] Comparative Example 2

[0079] The difference between this comparative example and Example 1 is that in this comparative example, no mica powder is added, and 23 parts of hematite powder are added.

[0080] Comparative Example 3

[0081] The only difference between this comparative example and Example 1 is that in this comparative example, hematite powder and mica powder are not added.

[0082] Experimental Example 1 Mechanical Properties Test

[0083] The thermal insulation composite materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were tested for tensile strength perpendicular to the surface according to the test method in GB / T 30804-2014 "Determination of tensile strength perpendicular to the surface of thermal insulation products for building". Before the test, the thermal insulation composite materials were prepared into samples with a size of 300 mm×300 mm and placed in an environment of 23°C for 6 hours. During the test, the constant speed was 10 mm / min, the number of samples was 5, and the test result was the average value of the 5 samples.

[0084] The test results are shown in Table 1 below:

[0085] Table 1 Mechanical properties test results of Examples 1 to 10 and Comparative Examples 1 to 3

[0086]

[0087] In Table 1, compared with Comparative Examples 1 to 3, the tensile strength perpendicular to the surface of Example 1 is significantly improved, indicating that when hematite powder and mica powder are introduced into the thermal insulation composite material, the hematite powder and mica powder have a synergistic effect and can improve the mechanical properties of the thermal insulation composite material.

[0088] Compared with Examples 2 and 4, the tensile strength perpendicular to the surface of Examples 5-6 is improved, indicating that when the weight ratio of hematite powder to mica powder is 2-5:1, the mechanical properties of the thermal insulation composite material can be further improved.

[0089] Compared with Example 6, the tensile strength perpendicular to the surface of Examples 7 to 10 is improved, indicating that when diphenylsilanediol is added to the binder, the mechanical properties of the thermal insulation composite material can be further improved. Compared with Examples 7 to 8, the tensile strength perpendicular to the surface of Examples 9 to 10 is improved, indicating that when the weight ratio of the organosilicon-modified epoxy resin to diphenylsilanediol is 5:1 to 2, the mechanical properties of the thermal insulation composite material can be further improved.

[0090] Experimental Example 2 High temperature resistance test

[0091] The thermal insulation composite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested for load shrinkage temperature according to the test method in GB / T 11835-2016 "Rock wool, slag wool and their products for thermal insulation". Before the test, the thermal insulation composite materials were prepared into a size of 1200 mm × 600 mm × 80 mm and a density of 150 kg / m 3 The number of samples is 2 and the test result is the average value of the 2 samples.

[0092] The test results are shown in Table 2 below:

[0093] Table 2 High temperature resistance test results of Examples 1 to 6 and Comparative Examples 1 to 3

[0094]

[0095] In Table 2, compared with Comparative Examples 1 to 3, the load shrinkage temperature of Example 1 is significantly increased, indicating that when hematite powder and mica powder are introduced into the thermal insulation composite material, the high temperature resistance of the thermal insulation composite material can be improved.

[0096] Compared with Examples 2 and 4, the load shrinkage temperature of Examples 5-6 is increased, indicating that when the weight ratio of hematite powder to mica powder is 2-5:1, the high temperature resistance of the thermal insulation composite material can be further improved.

[0097] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An iron-rich high temperature resistant heat insulating composite material, characterized in that: The invention comprises fibers and a binder, wherein the raw materials of the fibers include the following components in parts by weight: 35-45 parts of basalt, 20-32 parts of hematite powder, 10-16 parts of coke, 4-8 parts of ferrovanadium slag, 3-18 parts of mica powder; The raw materials of the binder include the following components in parts by weight: 8-17 parts of organosilicon-modified epoxy resin, 2-5 parts of siloxane copolymer, 3-6 parts of silicon dioxide, 1-3 parts of curing agent, 30 parts of solvent; The weight ratio of the fiber to the binder is 100:3-7.

2. The iron-rich high temperature resistant heat insulating composite material according to claim 1, characterized in that: The weight ratio of the hematite powder to the mica powder is 2-5:

1.

3. The iron-rich high temperature resistant heat insulating composite material according to claim 1, characterized in that: The raw materials of the binder also include 1 to 6 parts of diphenylsilanediol.

4. The iron-rich high temperature resistant heat insulating composite material according to claim 3, characterized in that: The weight ratio of the organosilicon-modified epoxy resin to the diphenylsilanediol is 5:1-2.

5. The iron-rich high temperature resistant heat insulating composite material according to claim 1, characterized in that: The content of silicon dioxide in the basalt is 48wt%~52wt%, the content of aluminum oxide is 10wt%~15wt%, and the particle size is 300~360 mesh; the content of iron oxide in the hematite powder is 65wt%~70wt%, and the particle size of the hematite powder is 200~325 mesh; the content of vanadium pentoxide in the ferrovanadium slag is 12wt%~14wt%, and the particle size is 200~325 mesh; the content of silicon dioxide in the mica powder is 55wt%~65wt%, the content of aluminum oxide is 15wt%~20wt%, and the particle size of the mica powder is 400~600 mesh.

6. The iron-rich high temperature resistant heat insulating composite material according to claim 1, characterized in that: The preparation method of the adhesive comprises the following steps: adding the organosilicon-modified epoxy resin, siloxane copolymer, silicon dioxide and curing agent into a solvent, and dispersing them uniformly to obtain the adhesive.

7. The iron-rich high temperature resistant heat insulating composite material according to claim 1, characterized in that: The curing agent is one or both of diaminodiphenylmethane and pyromellitic dianhydride; the solvent is one or both of toluene and xylene.

8. The method for preparing an iron-rich high temperature resistant heat insulating composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing, crushing and melting the raw materials of the fiber to obtain a molten liquid; S2, centrifuging and drawing the molten liquid to obtain the fiber; S3, spraying the binder on the surface of the fiber, and curing and shaping the fiber to obtain the thermal insulation composite material.

9. The method for preparing an iron-rich high temperature resistant heat insulating composite material according to claim 8, characterized in that: In step S1, the temperature during melting is 1320-1350°C.

10. The method for preparing an iron-rich high temperature resistant heat insulating composite material according to claim 8, characterized in that: In step S3, during the curing process, the curing temperature is 180-200°C.

Citation Information

Patent Citations

  • Basalt fiber composite material as well as preparation method and application thereof

    CN114988761A

  • Fireproof rock wool thermal insulation decorative board and preparation method thereof

    CN115557733A